Appendicular mucocele: presentation of three cases - Arpayoglou, Alejandro; Kamaid, Emil; Iraola, María L (Cirugía del Uruguay, 1973)
The authors present three cases of appendicular mucocele and consider its pathology, clinics and treatment.